PERANCANGAN MESIN PENGUPAS SABUT KELAPA SEMI OTOMATIS - Riyan Agustin (INOVTEK - SERI MESIN, 2022)
On generally stripping process fiber coconut in the community still many use method traditional where method traditional have a number of deficiency that is capacity small work where for peeling one fruit coconut eat time ± 1-5 minutes. Stripping with method traditional this still have many deficiency and weakness among them need great power, need people who have Skills special, risk caught eye knife , need a long time, and Position stripping less than ideal. designing and make machine peeler fiber semi automatic coconut with variation blade For knowing how much efficient variation on eye knife machine peeler fiber coconut. Study this conducted based on four stage, the first observation field, the second planning and design, the third assembly machine, and finally is To do testing. Machine peeler fiber semi automatic coconut that uses 3 shafts as a 2 shaft stripping medium lower as peeler with variation eye knife straight and inclined, 1 axis on what has been given rubber as press media fruit coconut to fruit coconut no bouncing when the stripping process take place. Machine this designed for make it easy and speed up the stripping process fruit coconut old with capacity 100 pieces/hour. Round axis stripping 23 rpm and round 2540 engine can produce capacity, Efficiency machine stripping fiber coconut with vary eye knife shaped straight and slanted in one axis this could peeling fiber coconut by whole with good, stripping style on fiber coconut 980 N dan power axis stripping 1179.58 Watts. Stripping fiber coconut need average time 37,26 second for 1 piece coconut old .